(3JjSjQ GdeWGdH aj CeGdi CHj WGdHs - (3GdbGVi TeS GdOjf LYaQ Hf CMeO Hf YHO GdSdGe Hf CHi jMjis; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3jhSa Hf YhGU Hf YHO Gddg s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi eG CfYe Hg ef GdgOGjI hGdOQGjI s
(3BNQgG (B:s
(3BNQg ef MOjK QShd Gddg Udi Gddg Ydjg hSde (B:" (3hYdjc HUfGFY GdNjQ aEfgG JOaY eUGQY GdShA (B" s
(3dfSNI ebGHdI hHChdgG bQGAI SfI (B643 (3g`s
(3hGdcJGH ai PcQ eYLRGJ GdfHi Udi Gddg Ydjg hSde hTeGFdg haVGFd Ydi Hf CHj WGdH hChdGOg QVi Gddg Yfges
(3hai aVd GdYde hGdLgGOs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs